Research on Strategies for Enhancing Core Competencies of International Students in China Based on the “Occupational Chinese Proficiency Standards” - Li, Ruikai; Qin , Jian (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed to 1) examine the multidimensional structure of core competency among international students in China under the “Chinese Language + Vocational Skills” education model, 2) analyze the relationships among psychological resilience, intercultural communication competence, occupational Chinese proficiency, vocational skills, and social support, and 3) explore the pathways that facilitate competency transformation from classroom learning to workplace application. The sample comprised 298 valid responses collected from 320 distributed questionnaires, yielding a valid return rate of 93.1%. Participants were full-time international students from three Chinese higher vocational colleges, representing 15 countries and regions across Southeast Asia, Central Asia, and Africa. Stratified random sampling was applied by gender, nationality, and major type. Data were collected between March and May 2024 using a structured questionnaire, including the Connor-Davidson Resilience Scale (CD-RISC-25), the Intercultural Communication Competence Scale (ICCS), an occupational Chinese proficiency test, a vocational skills self-assessment, and the Social Support Rating Scale (SSRS), supplemented by a researcher-developed comprehensive core competency scale. All scales demonstrated high internal consistency (Cronbach’s =0.82–0.91) and strong construct reliability (CR>0.80). Confirmatory factor analysis indicated good model fit (c2/df = 2.13, CFI = 0.94, TLI = 0.93, RMSEA = 0.052). Results revealed: 1) the five-dimensional model of core competency was well supported, with all factor loadings above 0.70 (p<0.001), 2) occupational Chinese proficiency fully mediated the effects of psychological resilience and intercultural competence on vocational skills, 3) social support had both direct and indirect positive effects on vocational skills development. The findings contribute to the theoretical understanding of integrated language-vocational education and provide actionable insights for enhancing curriculum design, teaching strategies, and support systems for international students in multicultural vocational contexts.